Introduction of large linear minichromosomes into Schizosaccharomyces pombe by an improved transformation procedure. - Allshire, R C (1990)
The efficiency of transformation of Schizosaccharomyces pombe has been increased 10- to 50-fold over previously reported methods. By using 1 microgram of plasmid, 7.0 x 10(5) transformants are regularly obtained. This increased transformation efficiency is mainly due to the inclusion of the cationic liposome-forming reagent Lipofectin in the protocol. Various parameters affecting transformation of Sc. pombe in the presence of Lipofectin have been examined. Lipofectin can also be used to increase transformation efficiency in Saccharomyces cerevisiae. It is also demonstrated that by using this improved transformation procedure, linear minichromosomes of greater than 500 kilobases can be introduced into Sc. pombe with relative ease. These minichromosomes can replicate as stable linear molecules upon reintroduction into Sc. pombe, demonstrating that Sc. pombe telomeres retain function when reintroduced as naked DNA. The ability of Sc. pombe to admit large DNA molecules indicates that it should be feasible to clone large DNA from other organisms in Sc. pombe.